2017
DOI: 10.14233/ajchem.2018.20932
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Spectroscopic Studies of Interaction of Clopidogrel Bisulphate with Calf Thymus DNA

Abstract: The DNA binding properties of clopidogrel bisulphate, was examined by cyclic voltammetry, fluorescence and UV spectroscopy. Shift in peak potential, decrease in peak current in cyclic voltammetry, hypochromic effect in UV titration and quenched emission intensity of ethidium bromide bound to calf thymus DNA signal indicated clopidogrel bisulphate has displaced ethidium bromide from its binding site in DNA. The binding constant is calculated using absorbance and is found to be closer to that estimated in voltam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It has been reported that administration of clopidogrel and aspirin to minor ischemic stroke patients had a lower risk of major ischemic events in comparison to patients with aspirin alone [30]. It has also been reported that ethidium bromide gets bound to calf thymus DNA signal that indicated clopidogrel bisulphate thus displacing ethidium bromide from its binding site of DNA [31]. Moreover, aspirin, being weaker acid, depresses the availability of clopidogrel bisulphate in basic media [32].…”
Section: Why There Is Need For a Nanocardiovascular Targeting Approachmentioning
confidence: 99%
“…It has been reported that administration of clopidogrel and aspirin to minor ischemic stroke patients had a lower risk of major ischemic events in comparison to patients with aspirin alone [30]. It has also been reported that ethidium bromide gets bound to calf thymus DNA signal that indicated clopidogrel bisulphate thus displacing ethidium bromide from its binding site of DNA [31]. Moreover, aspirin, being weaker acid, depresses the availability of clopidogrel bisulphate in basic media [32].…”
Section: Why There Is Need For a Nanocardiovascular Targeting Approachmentioning
confidence: 99%